Pengaruh Tabungan Wadiah dan Giro Wadiah Terhadap Laba Bersih PT Syariah Mandiri Periode 2013-2020 - Asmawiah, Siti Hajar; Sulistiyo, Hary (Fakultas Ekonomi dan Bisnis dan LPPM Universitas Negeri Jakarta, 2022)
This study aims to examine the effect of wadiah savings and wadiah current account on net profit at PT Syariah Mandiri. Sources of data used in this study is secondary data through the website www.bms.direghtion.com. This study uses a sample in the form of the financial statements of PT Syariah Mandiri published for the period 2013-2020. The data collection technique used is observation where the methods and techniques of data collection are by systematically observing and recording the symptomps or phenomena that exist in the object of research. The analytical method in this study uses multiple linear regression analysis and hypothesis testing. The results showed that profit will increase when wadiah saving increase. If all the operations of PT Syariah Mandiri can be carried out optimally, it will be very beneficial for PT Syariah Mandiri in obtaining profits.